Tales From the Arabian Nights - Edited by Foulds, David (Oxford Oxford University Press, 2005)
A cruel king marries beautiful young women, but always has their heads cut off in the morning. However, his new wife, Sheherezade, is clever. Every night, she starts to tell him a wonderful story. Every morning, the king lets his wife live, because he wants to hear the end of the story. Here, you can read some of Sheherezade's wonderful stories.
Include Color Illustration
Keywords: New literates, Writing for -- Tales -- Arab countries